Radish production under different shading screens and mulching - Cavalcante, Fábio; Sousa, Geocleber Gomes de; Freire, Márcio Henrique da Costa; Cruz Filho, Elizeu Matos da; Ribeiro, Rute Maria Rocha; Leite, Kelly Nascimento (Comunicata Scientiae, 2020)
Shading Screens and mulching may provide a favorable environment for radish growing in regions of adverse climates. This work aimed to evaluate the radish productivity under the influence of different shading screens associated with the presence and absence of mulch in two different years. The experiment was carried out in two different seasons (2017 dry season and 2018 rainy season), in the vegetable garden of Liberdade campus, at the University of International Integration of Afro-Brazilian Lusophony (Unilab), municipality of Redenção-CE. The experimental design was in randomized blocks in a split-plot arrangement, with four repetitions, in which the plots consisted of growing with and without mulching and in the subplots, five shading screens: 50% Black Shading Screen (50% BSS), 50% Red Shading Screen (50% RSS), 30% White Shading Screen (30% WSS), 70% Black Shading Screen (70% BSS) ), and full sunlight (FS). The red shading screens 50% and white 30%, in addition to cultivation under full sunlight, provide higher performance in terms of the number of leaves, tuberous root diameter, tuberous root matter, and the radish crop productivity, regardless of the evaluated period. The applied mulch does not influence the productivity of the rabante, influencing only the gain of dry mass of the aerial part, soluble solids and length of the tuberous root.